A PROPOSED THEORETICAL FRAMEWORK ON STRATEGIES FOR KLANG VALLEY MALAYSIAN QUANTITY SURVEYING CONSULTANCY FIRMS TO ACHIEVE PROFITABILITY - Bee-Ling Chong; Kai-Chen Goh; Tien-Choon Toh (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
There is a lack of research studies showing the specific practices that enable QS consultancy firms to achieve profitability in Malaysiaâ€™s construction industry. As firm profitability is expected to have a positive and significant impact on firm growth, this put Malaysia’s QS consulting firms at risk and affected firm growth if the problem they face remains unresolved. Despite the current Covid-19 pandemic has led to the global financial crisis, weaker global growth is still a big issue to developing countries including Malaysia. Construction firms such as QS consultancy firms face a lot of challenges due to the globalisation and competitiveness of the construction industry. Quantity surveying (QS) consultancy firms need to adopt suitable strategies to survive and grow in an evolving business environment. Thus, this paper focuses on the theoretical framework of the strategies for QS consultancy firms.